2018
DOI: 10.1155/2018/5969178
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Colombian Clay and Its Potential Use as Adsorbent

Abstract: This paper presents a mineralogical and physicochemical characterization of a Colombian clay found in an area with the greatest exploitation potential of smectites and possible use as an adsorbent for the removal of chromium. The clay was characterized by using X-ray diffraction (XRD), cation exchange capacity (CEC), X-ray fluorescence (XRF), Fourier transform infrared spectroscopy (FT-IR), thermal analysis (TGA/DSC), and nitrogen adsorption at 77 K. The homoionized clay was used as an adsorbent for the remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 57 publications
4
31
0
Order By: Relevance
“…e modification of the bentonite with the quaternary ammonium salt caused an increase in the basal spacing (d 001 ) of the layers from 1.6 nm to 2.1 nm brought about by HDTMA + cation intercalation. Macías-Quiroga et al [16] and Otavo-Loaiza et al [19] have reported similar basal spacing values for this bentonite and the bentonite modified with HDTMA-Br. e increase in the interlayer spacing indicates that the HDTMA + cations intercalated in the interlamellar space were arranged in the form of a pseudo-trimolecular layer [20].…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…e modification of the bentonite with the quaternary ammonium salt caused an increase in the basal spacing (d 001 ) of the layers from 1.6 nm to 2.1 nm brought about by HDTMA + cation intercalation. Macías-Quiroga et al [16] and Otavo-Loaiza et al [19] have reported similar basal spacing values for this bentonite and the bentonite modified with HDTMA-Br. e increase in the interlayer spacing indicates that the HDTMA + cations intercalated in the interlamellar space were arranged in the form of a pseudo-trimolecular layer [20].…”
Section: Resultssupporting
confidence: 54%
“…e large band at 1030 cm −1 corresponds to the Si-O stretching vibration. e above signals can be considered characteristic of dioctahedral smectite [16,23]. Broad bands centered near 3421-3427 cm −1 and 1636-1639 cm −1 are due to the-OH stretching mode of the interlayer water [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the removal of tartrazine from a solution using a modified bentonite are limited [41]. In Colombia, it has been estimated that smectite clay deposits for exploitation are 1.1 × 10 9 metric tons [42], which could be used as an adsorbent material. This study evaluates the effect of variables pH, ionic strength, agitation speed, adsorbent mass, and contact time on the adsorption of a tartrazine dye in an aqueous medium, using a Colombian bentonite modified with hexadecyltrimethylammonium bromide (HDTMA-Br) as the material adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, thermal stability and swelling behavior showed a strong relationship with the differences in the electrical charge of the layers, the origin of the charge deficiency, and interlayer cations [11]. Moreover, these features have motivated the study of Colombian clays in different fields such as environmental remediation, catalysts, and waste treatments [7,8,10,12]. Currently, commercial exploitation is mainly concentrated in animal feeding additives and cat litters.…”
Section: Introductionmentioning
confidence: 99%